Long‐Term miR‐669a Therapy Alleviates Chronic Dilated Cardiomyopathy in Dystrophic Mice. Issue 4 (20th August 2013) - Quattrocelli, Mattia; Crippa, Stefania; Montecchiani, Celeste; Camps, Jordi; Cornaglia, Antonia Icaro; Boldrin, Luisa; Morgan, Jennifer; Calligaro, Alberto; Casasco, Andrea; Orlacchio, Aldo; Gijsbers, Rik; D'Hooge, Jan; et al.
Abstract : Background: Dilated cardiomyopathy (DCM) is a leading cause of chronic morbidity and mortality in muscular dystrophy (MD) patients. Current pharmacological treatments are not yet able to counteract chronic myocardial wastage, thus novel therapies are being intensely explored. MicroRNAs have been implicated as fine regulators of cardiomyopathic progression. Previously, miR‐669a downregulation has been linked to the severe DCM progression displayed by Sgcb ‐null dystrophic mice. However, the impact of long‐term overexpression of miR‐669a on muscle structure and functionality of the dystrophic heart is yet unknown. Methods and Results: Here, we demonstrate that intraventricular delivery of adeno‐associated viral (AAV) vectors induces long‐term (18 months) miR‐669a overexpression and improves survival of Sgcb ‐null mice. Treated hearts display significant decrease in hypertrophic remodeling, fibrosis, and cardiomyocyte apoptosis. Moreover, miR‐669a treatment increases sarcomere organization, reduces ventricular atrial natriuretic peptide (ANP) levels, and ameliorates gene/miRNA profile of DCM markers. Furthermore, long‐term miR‐669a overexpression significantly reduces adverse remodeling and enhances systolic fractional shortening of the left ventricle in treated dystrophic mice, without significant detrimental consequences on skeletal muscle wastage. Conclusions: Our findings provide the first evidence of long‐term beneficial impact of AAV‐mediated miRNA therapy in a transgenic model of severe, chronic MD‐associated DCM.